2020
DOI: 10.1002/jcph.1678
|View full text |Cite
|
Sign up to set email alerts
|

Can PBPK Modeling Streamline Food Effect Assessments?

Abstract: Physiologically based pharmacokinetic (PBPK) modeling is routinely used to study drug-drug interactions, replace some dedicated clinical studies, and inform product labeling. More recently, there has been increased application of PBPK models in the oral absorption field around drug product quality. Given the success of the models to characterize absorption of several orally administered drug products, a question arises whether PBPK could be used in a clinical setting to model food-drug interactions and thus st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…The application of physiologically based pharmacokinetic (PBPK) models can help the formulation scientist to further explore the impact of any formulation, physiology, or population parameter on the systemic exposure of the drug. Sensitivity analyses can be performed to judge which parameters play a pivotal role in the absorption process. Moreover, if any formulation changes would be made during the clinical or postapproval phase of drug product development, these changes can be explored in the modeling software to directly anticipate the impact of these changes on the systemic outcome of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…The application of physiologically based pharmacokinetic (PBPK) models can help the formulation scientist to further explore the impact of any formulation, physiology, or population parameter on the systemic exposure of the drug. Sensitivity analyses can be performed to judge which parameters play a pivotal role in the absorption process. Moreover, if any formulation changes would be made during the clinical or postapproval phase of drug product development, these changes can be explored in the modeling software to directly anticipate the impact of these changes on the systemic outcome of the drug.…”
Section: Introductionmentioning
confidence: 99%
“…It has become increasingly plausible that PBPK models can be used for assessing drug-drug interaction, dose adjustment during renal or hepatic impairments, pediatric dose adjustment, and biopharmaceutics-related assessment with notable success in new drug development. [1][2][3][4] Acceptability of these models has further been exemplified through the publication of PBPK guidances by both the FDA and European Medicines Agency in recent years. 5,6 In fact, the FDA's Office of Generic Drugs frequently uses mechanistic modeling and simulation approaches to support regulatory decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the application of oral PBPK models for assessing food impact 16–23 . In addition, some reports have also pointed out the prospects and challenges related to the use of PBPK for assessing the impact of food 1,24 . However, there still exists a knowledge gap regarding the appropriate development, validation, and use of PBPK modeling approaches for food effect assessment, specifically for regulatory submission purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis suggested that PBPK models developed based on in vitro solubility, permeability, and dissolution in conjunction with PK data under fasting conditions may be a useful tool to assess food effect; however, factors such as the effect of food on the activity of enzymes and transporters and differences in how various physiological processes are parameterized across software platforms hinder the widespread application of PBPK for prospective food‐effect evaluation. In this supplement, Kesisoglou further explores if PBPK modeling can streamline food effect assessments 10 . In addition to a summary of advancements made in the area of using PBPK for predicting the effect of food and current knowledge gaps, a workflow to use PBPK to facilitate the assessment of food effect in drug development is proposed.…”
mentioning
confidence: 99%